PERBANDINGAN LUARAN KLINIS PASCA OPERASI TRANSFEMORAL AORTIC VALVE REPLACEMENT DENGAN SURGICAL AORTIC VALVE REPLACEMENT PADA PASIEN STENOSIS AORTA BERAT YANG RENDAH RISIKO TERHADAP PEMBEDAHAN: Systematic Review - Tegar Wirayudha, (2023)
Aortic stenosis patients are numerous and the use of TAVI have been widespread, even in low-risk patients for surgery. However, postoperative events such as stroke and myocardial infarction may occur with TAVR or SAVR. Based on this background, the authors wanted to compare clinical outcomes after TAVI with SAVR in symptomatic severe aortic stenosis patients who were at surgical low risk. The research design used in this study was a literature review with a systematic review method. This research was conducted by searching for publication data of a study using a search engine followed by drawing conclusions to get new results or conclusions or refute existing opinions. The six journals selected discussed the incidence of death from various causes, death from cardiovascular causes, stroke, and myocardial infarction. Five of the journals showed no statistically significant difference between TAVR and SAVR. This indicates that intervention with TAVR is not better than SAVR. However, in one journal it was found that there was a difference between the two interventions statistically as evidenced by the Confidence Interval. The clinical outcomes analysed are still inconsistencies in the incidence of TAVR compared to SAVR. TAVR in patients with severe aortic stenosis with low surgical risk can be an option, but is still not good enough as a guideline for therapy. Development of a new generation of transcatheter valves and long-term follow-up is needed to compare TAVR and SAVR in patients with severe aortic stenosis with low surgical risk.